The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/are.12805
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of juvenile pacu (Piaractus mesopotamicus) and dourado (Salminus brasiliensis) fed with lyophilized bovine colostrum

Abstract: Growth performance was evaluated in juvenile pacu (Piaractus mesopotamicus) and dourado (Salminus brasiliensis) fed diets containing 0%, 10% and 20% of lyophilized bovine colostrum for 60 days. The performance variables of weight gain, relative weight gain, feed intake, feed conversion ratio, specific growth rate, total protein intake and protein efficiency ratio were evaluated as well as apparent digestibility coefficients of protein and energy in the diets. Inclusion of bovine colostrum did not induce differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Working with the same kind of fish of the present study, Machado‐Neto et al . () observed reduction in specific growth rate at 60 days, supporting the idea of slowdown fish growth. The present study suggests great capacity to synthesize intracellular proteins by muscle cells from younger fish, positively related with fish growth, like was found by Stierhoff, Targett and Power ().…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Working with the same kind of fish of the present study, Machado‐Neto et al . () observed reduction in specific growth rate at 60 days, supporting the idea of slowdown fish growth. The present study suggests great capacity to synthesize intracellular proteins by muscle cells from younger fish, positively related with fish growth, like was found by Stierhoff, Targett and Power ().…”
Section: Discussionsupporting
confidence: 54%
“…After adaptation period (10 days) to experimental routine, fish were hand‐fed ad libitum to apparent satiety (08:30 and 16:30 hours) with the pelleted control diet containing 0% of LBC or experimental diet containing 10% and 20% of LBC inclusion, for either 30 or 60 days of experiment. Machado‐Neto, Moretti, Nordi, Cruz and Cyrino () working with the same experimental conditions and fish species, pacu, did not observed difference in feed intake of juveniles fed diets with or without colostrum, revealing that the colostrum is palatable to this species. The survival record during the experimental period for pacu fed 0% LBC was 92% at 30 days and 100% at 60 days.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Dourado (W 0 = 5.68 g) fed diets (45 % CP and 4098 kcal kg -1 ) based on FM (41 % of diet) and casein (16 %) as dietetic protein sources had 39 g of WG and a protein retention of 26.58 %, in 94 d (Teixeira et al, 2010). Machado-Neto et al (2015) conducted a 60-day experiment and found that dourado (W 0 = 13.3 g) fed a control diet (44 % CP and 4967.99 kcal kg -1 ) based on FM (32 % of diet), poultry by-product meal (20 %) and SBM (23 %), obtained a WG of 55.6 g and a PER of 1.1. Lorenz et al (2018) reported WG 26.02 g and PER 2.22, when dourado (W 0 =4.57g) were fed a control diet (45 % CP and 4793.64 kcal kg -1 ) based on FM (28 % of diet), corn gluten meal (13 %) and SBM (31 %) for 61 d. All reports mentioned above presented diets with the same protein for gross energy ratio (0.01), as well as experimental diets used in this study.…”
Section: Initialmentioning
confidence: 99%
“…This species is easily adaptable to intensive production in cages (Hilbig et al 2012;Bittencourt et al 2010); however, in ponds, low production density varying from 0.5 to 2 kg m −2 is usually reported (Valladão et al 2018). The technical viability of pacu culture in closed systems was described only for larviculture (Jomori et al 2003) and juvenile production (David et al 2019a;Machado-Neto et al 2016) phases, while no information on commercial or experimental production in RAS for the growth-out phase is available. In aquaponics systems, pacu is commonly reported as a species that is already being produced (Yep and Zheng 2019;Martins 2017;Rakocy 2012).…”
Section: Pacu (Piaractus Mesopotamicus)mentioning
confidence: 99%